Inhibitory Effect of the Melanocortin Receptor Agonist Melanotan-II (MTII) on Feeding Depends on Dietary Fat Content and not Obesity in Rats on Free-Choice Diets - van den Heuvel, José K.; Eggels, Leslie; van Rozen, Andrea J.; Fliers, Eric; Kalsbeek, Andries; Adan, Roger A. H.; la Fleur, Susanne E. (Frontiers in Behavioral Neuroscience, 2015)
Introduction: Conflicting data exist on sensitivity changes of the melanocortin system during diet-induced obesity. We hypothesized that melanocortin sensitivity depends on diet composition, in particular on the fat content rather than the level of obesity. The aim of this study was to determine the influence of diet composition on feeding responses to a melanocortin receptor agonist, using free-choice diets that differ in food components. Methods: Male Wistar rats were subjected to a chow (CHOW) diet or a free-choice (fc) diet of either chow, saturated fat and liquid sugar (fcHFHS), chow and saturated fat (fcHF), or chow and liquid sugar (fcHS) for 4 weeks. Melanocortin sensitivity was tested by measuring food intake following administration of the melanocortin 3/4 receptor agonist melanotan II (MTII) or vehicle in the lateral ventricle. In a separate experiment, proopiomelanocortin (POMC) and agouti-related protein (AgRP) mRNA levels were determined in the arcuate nucleus with in situ hybridization in rats subjected to the free-choice diets for 4 weeks. Results: Rats on the fcHFHS diet for 4 weeks show increased caloric intake and body weight gain compared to rats on the CHOW, fcHS and fcHF diet. Caloric intake and body weight gain was comparable between rats on the fcHF, fcHS, and CHOW diet. After 4 weeks diet, POMC and AgRP mRNA levels were not different between diet groups. MTII inhibited caloric intake to a larger extent in rats on the fcHF diet compared to rats on the CHOW, fcHFHS or fcHS diet. Moreover, the fat component was the most inhibited by MTII, and the sugar component the least. Conclusion: Rats on the fcHF diet show stronger food intake inhibition to the melanocortin receptor agonist MTII than rats on the CHOW, fcHS, and fcHFHS diet, which is independent of caloric intake and body weight gain. Our data point toward an important role for diet composition, particularly the dietary fat content, and not obesity in the sensitivity of the melanocortin system.